Деонтологічні засади забезпечення соціального партнерства за участю міліції - Козік, М.А. (Альманах права, 2012)
У статті охарактеризовано деонтологічні засади забезпечення соціального партнерства за участю міліції; розглянуто основні деонтологічні принципи, на яких базується соціальне партнерство міліції з громадськими та державними суб’єктами у правоохоронній сфері; визначено роль деонтології в діяльності міліції. В статье дана характеристика деонтологических основ обеспечения социального партнерства с участием милиции; рассмотрены основные деонтологические принципы, на которых базируется социальное партнерство милиции с общественными и государственными субъектами в правоохранительной сфере; определена роль деонтологии в деятельности милиции. The deontological basis of social partnership police are characterized in the article. The basic deontological principles underlying social partnership with civil police and governmental entities in law enforcement are examined. The main deontological principles are respect, kindness, justice, honesty, responsibility, control, balance. These principles can be considered not only as the general standards of conduct, but also as principles that allow police to improve cooperation with local communities and their community groups. Social partnership with police and state bodies is based on free will, trust, respect and equity partnershiop. These requirements may follow mainly by moral guidelines. The positive experience of foreign countries police indicates the need to develop international standards based on their promising ways to interact with the public. Nowadays there is a tendency to create universal standards of officers’ conduct in law enforcement. Each country has its own national characteristics, the history of the formation of social institutions, the concept of the state system, a system of views on professional ethics and deontology police, especially the formation of the Police. In view of integration processes need to develop common standards for operation of the most important social and legal institutions including police. A specific object of deontological regulation of the police is the ratio of its and public interests. Deontological regulation mechanism is the set of influence means onto police. Internal sources of self-regulation of this mechanism are necessity of implementation the behavior of police officers. The human life is criteria by which is created police needs. There is strict interaction between personal needs and inner world of individual, social activity and moral behavior. Hence the task of the education is to form individual needs, which would coincide with the requirements of society. The principles of legal ethics are not exhaustive, it complements each other. The main of them are the following: humanity means a respectful attitude partners and their rights, personal characteristics and interests; justice ensures that the police will act impartially and in accordance with law; honesty this principle is very important for the image of the police, it involves not only the honesty but also openness to himself; responsibility the principle requires police and other agents of social partnership be responsible for their actions; control requires a kind of control over the actions of partners and associated with the previous principle. Thus, the activities of the police are social control; normativity means relationships are subject to certain standards. This is not necessarily legal rules, it may be moral norms, especially partner own rules, which he produced under the influence of various factors; timeliness — this principle means that police officers always should be informed in time to take the optimal solution. Even a small delay significantly affects the performance, the final result. In was defined the role of ethics in police work. It was proved that deontological principles in the work of police and social partnership in particular aim to ensure high relevance to humans. On the law enforcement agencies protect the interests of the person’s life, honor and dignity. It is important for society to increase quality of police officers professional duty. The main purpose of partnership is to strengthen law and order, protection of citizens from illegal encroachments, improving the legal culture and legal awareness, and creating a positive image of law enforcement. Deontological principles of humanity, benevolence, justice, honesty, normativity consider general standards of conduct. They allow police to improve cooperation with local communities.